Public service announcement : a way to develop students' speaking skills - Jamari, Suzilla (Penerbit UTHM, 2020)
Developing second language learners' speaking skills requires a lot of effort from both the educators and the students themselves. This is due to the many aspects involved such as pronunciation, stress, intonation, and message. Educators need to make sure that the selected speaking activities can enhance students' speaking ability whereas students need to give their commitment in doing the tasks assigned to them. Collaboration and cooperation from both parties will ensure the hours spent for the teaching and learning of this skill yield a fruitful result.